2018
DOI: 10.1016/j.dsr.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesoscale structures on the distribution of cephalopod paralarvae in the Gulf of California and adjacent Pacific

Abstract: 24Vertical distribution of the cephalopod paralarvae was investigated in relation to a system 25 of two cyclonic and three anticyclonic eddies in the southern Gulf of California and a front 26 in the adjacent Pacific Ocean. Results showed that the preferential habitat for the 27 Sthenoteuthis oualaniensis -Dosidicus gigas "SD-complex" in both regions was the 28 oxygenated surface mixed layer and the thermocline. The highest abundances occurred in 29 of one of the anticyclonic eddies and a frontal zone, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In oceanic regions where dissolved oxygen is already low, such as the shallow oxygen minimum zones (OMZs) of the eastern North Pacific Ocean (Cepeda‐Morales et al, ; Schmidtko et al, ; Stramma et al, ), the deoxygenation process can affect the habitat of pelagic organisms from zooplankton to top predators (Diaz & Rosenberg, ; Ekau et al, ; Hofmann et al, ; Longhurst, ; Prince & Goodyear, ). Previous studies in this shallow OMZ (Fernandez‐Alamo & Farber‐Lorda, , Sánchez‐Velasco et al, , 2017, Ruvalcaba‐Aroche et al, ) reported that the zooplankton biomass and total larval fish and cephalopod paralarvae had the highest abundances in the oxygenated surface layer (>44 μmol/kg) and decreased toward the hypoxic (<44 μmol/kg) and suboxic (<4.4 μmol/kg) conditions of the deeper layers. This is similar to findings on the vertical distribution of zooplankton in other shallow OMZs in the southeastern Pacific, Benguela and Angola Currents, and the Arabian Oceans (Madhu et al, , Ekau & Verheye, , Escribano et al, , Hirche et al, ).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In oceanic regions where dissolved oxygen is already low, such as the shallow oxygen minimum zones (OMZs) of the eastern North Pacific Ocean (Cepeda‐Morales et al, ; Schmidtko et al, ; Stramma et al, ), the deoxygenation process can affect the habitat of pelagic organisms from zooplankton to top predators (Diaz & Rosenberg, ; Ekau et al, ; Hofmann et al, ; Longhurst, ; Prince & Goodyear, ). Previous studies in this shallow OMZ (Fernandez‐Alamo & Farber‐Lorda, , Sánchez‐Velasco et al, , 2017, Ruvalcaba‐Aroche et al, ) reported that the zooplankton biomass and total larval fish and cephalopod paralarvae had the highest abundances in the oxygenated surface layer (>44 μmol/kg) and decreased toward the hypoxic (<44 μmol/kg) and suboxic (<4.4 μmol/kg) conditions of the deeper layers. This is similar to findings on the vertical distribution of zooplankton in other shallow OMZs in the southeastern Pacific, Benguela and Angola Currents, and the Arabian Oceans (Madhu et al, , Ekau & Verheye, , Escribano et al, , Hirche et al, ).…”
Section: Introductionmentioning
confidence: 69%
“…On the basis of previous studies that described latitudinal dissolved oxygen gradients from SE to NW (Cepeda‐Morales et al, ; Davies et al, ; Ruvalcaba‐Aroche et al, ) and the marine ecoregions defined according to species distribution (Santamaría‐del‐Ángel et al, ), the dissolved oxygen profiles were divided into two regions: the north zone located at the mouth of the Gulf of California and the south zone off Cabo Corrientes (Figure a). Particularly, the northwest conductivity, temperature and depth (CTD) stations (between 20.5°N and 23°N) are considered part of the north zone according to the Gulf of California marine ecoregion mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant members of this cephalopod community are abundant in the temperate and tropical global oceans (Bower et al., 1999; Brodeur & Yamamura, 2005; Judkins, Vecchione, Cook, & Sutton, 2017; Lischka, Piatkowski, & Hanel, 2017; Reid, 2016; Ruvalcaba‐Aroche et al., 2018; Voss, 1980) and broadly represent the diversity of activity levels exhibited by cephalopods in oceanic ecosystems. To further validate and expand the applicability of this functional approach of community trophic structure will require testing in additional ecosystem types.…”
Section: Discussionmentioning
confidence: 99%